Innovative Selling A Guide to Successful Corporate Professional Selling. - White, Eden (Issn Ser., 2020)
Innovative selling is a unique book for corporate sales professionals and their sales leaders about how to prepare, manage, cope, and succeed at corporate global sales. Recent research has discovered concerning underlying discontent with professional sales people who represent global sales organizations. This book assists the sales professionals with navigating the dilemmas and pitfalls that confront today's corporate sellers so they emerge at the other end mentally healthy, skilled, and sane. The book also tackles and simplifies the basic steps of the overall sales process, territory planning, and product training, so as to ultimately improve your sales results. Many sales people today are looking for a simple and concise book to guide them through the corporate sales process-this is the book for you.